The openness of Open Application Programming Interfaces - Qiu, Yuanbo (Information, communication & society, 2017)
As a way to provide services or data to third-party developers, Open Application Programming Interfaces (Open APIs) have gained popularity among the programming community in recent years. Many corporations such as Google, Facebook and Twitter are developing Open APIs for their existing services, and most of them are free of charge. As these free APIs facilitate collaboration between different software platforms, many programmers treat them as alternatives to open source. Yet, some programmers have found this collaboration risky to their independence, and they have started to think about the true meaning of the openness of API. More importantly, the definition of Open APIs is rendered ambiguous through the discursive practices that define 'openness' in contemporary digital culture. Drawing on the political economy of programming and software, this study begins with the historical discussion of openness and its relationship with the power of code in programming. It points out the openness in programming is not only about the accessibility of the source code, but also the liberty to use source code without restriction. This paper then identifies the technical features of Open APIs and examines the subtle power that restricts their openness. It concludes by suggesting ways to critically understand the openness of software and their politics.